2015
DOI: 10.1111/1759-7714.12312
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and strategy for left tracheobronchial lymph node dissection in thoracolaparoscopic esophageal cancer surgery

Abstract: BackgroundThis study evaluates the feasibility and strategy of left tracheobronchial lymph node (LN) dissection in the surgical treatment of esophageal cancer, and its impact on surgical outcomes following thoracoscopic esophagectomy.MethodsData of 265 patients with thoracic esophageal cancer who underwent thoracoscopic and laparoscopic esophagectomy was retrospectively reviewed. In 80 cases, thoracoscopic esophagectomy was performed without left tracheobronchial LN dissection (group non‐4L), while 185 cases u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
2
8
1
3
Order By: Relevance
“…These complications included the following: pneumonia, anastomotic leakage, vocal cord palsy, gastrointestinal dysfunction, cardiovascular disease, and chylothorax. [8] There was no statistically significant difference in the incidence of major complications.…”
Section: Resultsmentioning
confidence: 96%
“…These complications included the following: pneumonia, anastomotic leakage, vocal cord palsy, gastrointestinal dysfunction, cardiovascular disease, and chylothorax. [8] There was no statistically significant difference in the incidence of major complications.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies from Japan have shown the benefits of MIE in the prone position in terms of better surgical exposure, a larger number of dissected lymph nodes and less blood loss compared to MIE in the left lateral decubitus position. However, most cases undergo MIE in the left lateral decubitus or semi‐prone position in China . It is difficult to obtain better operative exposure around the left RLN in this position because the collapsed right lung and mediastinal organs and structures move to the left side, which deepens the location of the left RLN.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential following lymphadenectomy along the RLN during esophagectomy for accurate pathological staging and prognostic evaluation, but does require more advanced and reliable dissection skills . Although thoracoscopic lymphadenectomy, particularly along the left RLN, is thought to be a burdensome step, with potential difficulties arising during operative exploration in the left lateral decubitus position, which may also lead to a potential increase in the risk of RLN damage, however, it is considered reliable and feasible in experienced hands …”
Section: Introductionmentioning
confidence: 99%
“…Авторы [15,16,18] демонстрируют противоречивые результаты по частоте его повреждения, но статистически значимые различия между двумя группами отсутствуют. При этом применение оригинальных методик лимфоаденэктомии позволяет улучшить данные показатели как в группе LD [9], так и в группе PP [19].…”
Section: обзор Reviewunclassified
“…[8], которые провели сравнительный анализ эзофагэктомий у 447 пациентов, 324 из них прооперированы традиционным способом, а 123 -из МИД. Авторы отметили, что количество удаляемых лимфатических узлов при МИЭ и ОЭ существенно не различалось (20,4±3,8 и 21,1±4,3 соответственно; p=0,0944), однако при ОЭ, выполняемой из правостороннего доступа, количество лимфатических узлов, удаляемых в зоне левого возвратного гортанного нерва, было больше, чем при МИЭ (80,2 и 43,9%; р<0,001), что, очевидно, связано с выбором позиции больного во время грудного этапа удаления пищевода (lateral decubitus и prone position) и техники выполнения лимфодиссекции [9,10].…”
unclassified